Technological Strategies and Performance of the Judicial Sector in Kenya: A Case of Nairobi City County - Mulwa, A.; Ngala, M.; Mugaa, L. (European Journal of Business and Strategic Management, 2023)
Purpose: Innovations and rapid diffusion of information and communication technologies in institutions are currently experiencing revolutionizing organizational processes. Globalization equally fuels the adoption of the ICT as the basis for digital operations are changing the way organizations operate. Studies on various countries' courts show that the judicial efficiency affects a country "˜s entrepreneurial activities; this reduces as the level of inefficiency increases. Thus, the study sought to analyze the influence technological strategies on performance of judicial sector in Kenya. Specifically, the study proposed to determine the influence of technological sourcing; technology posture; technological culture change; technological capacity on the performance of the judicial sector in Kenya. Methodology: By adopting descriptive research design, the study targeted all the five magistrate courts in Nairobi City County and purposively targeted nine offices per station, comprising (magistrate, court clerk, court accountant, court secretaries, court Archivist, HR and Administration officer, ICT officer, Procurement officer, and Library assistant, yielding a total of 45 sample size respondents for the study. Primary data was collected through structured questionnaires, which was piloted to ascertain its reliability and validity. Data was analyzed both descriptively as well as inferentially with the help of SPSS program (v.25.0) and MS Excel 10 softwares; and results presented using tables and charts for interpretation. Findings: From the study results, all the technological strategies variable had a positive and significant relationship with performance of the judicial sector in Nairobi City County in Kenya. Unique Contribution to Theory, Practice and Policy: The study was formed by the following theories: Transactional Cost, knowledge based; Stakeholders; Culture theory as well as the Task-technology fit theory. The study recommended that magistrate courts in Nairobi City County in Kenya should enhance their technological strategies since the strategies have been shown to bear a positive and significant effect on performance. The magistrate courts can achieve this through adopting advance technological orientations, especially where sourcing and culture of operations are concerned.